(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2025)
The duality of the trill ŕ was first detected in the southeastern Iberian writing in the lead of La Bastida, where the marked variant appears almost always in an intervocalic position. In contrast, in northeastern Iberian writing its use is more irregular, but with the non-marked variant preferably in an intervocalic position, with the value of the mark inverted, as in the occlusives. The northeastern duality was confirmed when appearing in the Tos Pelat abecedary and for an almost regular intervocalic use of the non-marked variant in the Xàbia lead. The surprise was the appearance of this duality in the hand of Ilulegi, in a non-dual context and with irregular behavior. The purpose of this work is to refine the behavior of this duality in northeastern scripts and to confirm that its aim was to distinguish the simple trill (tap) from the multiple (trill).